Penerapan Flood Early Warning System (Flews) Sebagai Upaya Mitigasi Banjir di Kelurahan Sungai Nangka Balikpapan Selatan - Widodo Widodo; Retno Kusniyawati; Hilma Garwydan; Azel Muhammad Tsaqif; Farrel Prayoga Susantha; Farraas Sajida; Nabila Putri Primadi; Dina Ayu Aulia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Balikpapan is a city with an average high rainfall of 259.229mm/year. The high rainfall, geological conditions, topographical conditions and land use are several factors that cause frequent flooding in this city. The problem of flooding in Balikpapan city is a strategic issue in the RPJPD of Balikpapan City 2005-2025. Sungai Nangka Village, South Balikpapan, especially in RT 45 is a flood-prone area where every rain with high intensity coupled with rising sea water entering this area makes this area often flooded. This community service aims to help RT 45 residents Kelurahan Sungai Nangka to carry out flood mitigation in an effort to reduce the greater impact of frequent flood disasters so that environmental quality improves. This community service method is to install a Flood Early Warning System (Flews) at RT 45 Nangka River, South Balikpapan. This system uses sensor and IoT technology. Through the Flews tool that has been installed on the RT 45, it is hoped that early warning of potential flooding will be received by local residents and related agencies through applications on smartphones in real time so that floods and their impacts can be earlier and can be anticipated thereby reducing the wider negative impacts for local residents, both material and nonmaterial impacts.